Finance in Islamic Marriage and Following Its Dissolution - A Comparison with Polish Legal Regulations - Frańczuk, Magdalena (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The paper presents the financial issues in Muslim marriage and dissolution of marriage by divorce. Because of the norms regarding inheritance, I do not focus on the law of succession, which also carries very significant financial implications for the heirs of a deceased spouse, and thus issues related to the topic as the subject of the present work. The paper refers frequently to J. Bielawski's translation of the Koran, as well as to the regulations of the Polish Family and Custody Code and to the literature and Internet sources on that topic. In principle the elaboration has a legal-comparative character.